Addition of Benzonitrile Oxide to 3,4,5-Trimethoxy-benzalanilines and Evaluation of Products as Antifungal Agents - Manrao, M.R.; Kanta, Chander (Asian Journal of Chemistry, 2010)
1,2,4-Oxadiazolines were prepared by the addition of benzonitrile oxide to 3,4,5-trimethoxybenzalanilines. The cycloadducts were identified and confirmed on the basis of elemental analysis and spectral studies. The products were tested in vitro for their antifungal activity against Alternaria tenuis, Ustilago tritici, Sphaeceloma maydis, Puccinia recondita and Alternaria triticina.